Using a mass media campaign to raise women's awareness of the link between alcohol and cancer: Cross-sectional pre-intervention and post-intervention evaluation surveys - Dixon, H.; Pratt, Steve; Scully, M.; Miller, J.; Patterson, C.; Hood, R.; Slevin, Terry (BMJ Publishing Group, 2015)
Objectives To evaluate the effectiveness of a population-based, statewide public health intervention designed to improve women's awareness and knowledge of the link between alcohol and cancer. Design: Cross-sectional tracking surveys conducted pre-intervention and post-intervention (waves I and III of campaign). Setting: Western Australia. Participants: Cross-sectional samples of Western Australian women aged 25–54 years before the campaign (n=136) and immediately after wave I (n=206) and wave III (n=155) of the campaign. Intervention: The ‘Alcohol and Cancer’ mass media campaign ran from May 2010 to May 2011 and consisted of three waves of paid television advertising with supporting print advertisements. Main outcome measures: Campaign awareness; knowledge of drinking guidelines and the link between alcohol and cancer; intentions towards drinking. Results: Prompted recognition of the campaign increased from 67% following wave I to 81% following wave III (adjusted OR (adj OR)=2.31, 95% CI 1.33 to 4.00, p=0.003). Improvements in women's knowledge that drinking alcohol on a regular basis increases cancer risk were found following wave I (adj OR=2.60, 95% CI 1.57 to 4.30, p<0.001) and wave III (adj OR=4.88, 95% CI 2.55 to 9.36, p<0.001) compared with baseline. Knowledge of the recommended number of standard drinks for low risk in the long term increased between baseline and wave I (adj OR=1.68, 95% CI 1.02 to 2.76, p=0.041), but not baseline and wave III (adj OR=1.42, 95% CI 0.84 to 2.39, p=0.191). Among women who drink alcohol, the proportion expressing intentions to reduce alcohol consumption increased significantly between baseline and wave III (adj OR=2.38, 95% CI 1.11 to 5.12, p=0.026). However, no significant reductions in recent drinking behaviour were found following the campaign.Conclusions: Results indicate a population-based mass media campaign can reach the target audience and raise awareness of links between alcohol and cancer, and knowledge of drinking guidelines. However, a single campaign may be insufficient to measurably curb drinking behaviour in a culture where pro-alcohol social norms and product marketing are pervasive.